Evaluating bevacizumab in combination with FOLFIRI after the failure of platinum-etoposide regimen in patients with advanced poorly differentiated neuroendocrine carcinoma: The PRODIGE 41–BEVANEC randomized phase II study. Issue 2 (February 2018) - Walter, Thomas; Malka, David; Hentic, Olivia; Lombard-Bohas, Catherine; Le Malicot, Karine; Smith, Denis; Ferru, Aurélie; Assenat, Eric; Cadiot, Guillaume; Lievre, Astrid; Kurtz, Jean-Emmanuel; Dahan, Laetitia; et al.
Abstract: Introduction: Patients with gastroenteropancreatic (GEP), metastatic or locally advanced, non-resectable, grade 3 poorly-differentiated neuroendocrine carcinoma (NEC) are treated with cisplatin (or carboplatin)-etoposide in first-line palliative chemotherapy (CT1). However, nearly all patients will develop resistance and there is no standard second-line treatment. Aim: PRODIGE 41–BEVANEC is an academic randomized, phase II study designed to evaluate the efficacy of bevacizumab in combination with FOLFIRI after failure of CT1 in unknown primary NEC and GEP-NEC. Materials and methods: The main eligibility criteria are age ≥18 years, metastatic (synchronous or metachronous) or locally advanced, non-resectable, grade 3 GEP-NEC, and documented progressive disease during or after CT1 therapy. Results: A total of 124 patients will be randomly assigned (1:1) to receive either 5 mg/kg bevacizumab with FOLFIRI, or FOLFIRI alone, every 14 days until disease progression or unacceptable toxicity. The hypothesis is to demonstrate a 6-month overall survival for at least 50% of the patients in bevacizumab arm versus 35% in the control arm (FOLFIRI alone). Secondary endpoints are objective response, response duration, progression-free survival, toxicity, and biochemical response. Conclusion: The study is currently opened in France (NCT02820857). The first patient was randomized on September 6, 2017.